Sertoli cells as a hub in testicular development and male reproductive - Feng, Xianzhou; Tian, Jiahui; Han, Shuaiqi; Wen, Fei; Li, Yu; Zhang, Shuaihang; Ouyang, Lidi; Hu, Zhangtao; Chen, Xiaoxu; Hu, Jianhong (Frontiers in Cell and Developmental Biology, 2025)
In the early stages of mammalian embryonic development, the bipotential gonads can differentiate into the testes or ovaries. These organs are essential for gamete production, transmitting genetic information to offspring via sperm or oocytes. Testis differentiation is triggered by the Y chromosome sex-determining region (SRY) genetic program, with male reproductive health largely established during the early stages of testis development. However, SRY is only transiently activated in precursor Sertoli cells, initiating their differentiation. At later stages, differentiated Sertoli cells are crucial for male sex determining in other cell lineages, including germ cells, Leydig cells involved in steroid hormone synthesis, and the establishment of vascular patterns. Clearly, Sertoli cells play an essential role in testis development and function, and are indispensable for male reproduction. In this review, we examine the composition and functional dynamics of the testis, highlighting how single-cell transcriptomics has redefined our understanding of testicular cellular architecture and functional diversity. We focus on the pivotal regulatory roles of Sertoli cells in orchestrating the development and functional coordination of germ cells, Leydig cells, peritubular myoid cells, and testicular macrophages. Furthermore, we discuss the pathological consequences of Sertoli cell dysfunction and its mechanistic contributions to male reproductive disorders, providing molecular insights into spermatogenic failure and androgen dysregulation.